2022
DOI: 10.1007/s00586-022-07159-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of laminectomy with fusion and laminectomy alone in degenerative cervical myelopathy

Abstract: Purpose The effectiveness of laminectomy with fusion and laminectomy alone in degenerative cervical myelopathy was compared. Methods Individuals treated with laminectomy with fusion or laminectomy alone at or below the second cervical vertebra were identified in the Swedish spine registry. 66 individuals treated with laminectomy and instrumented fusion were age matched to 132 individuals treated with laminectomy alone. The European Myelopathy Scale (EMS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…However, the results are consistent with previous, smaller, studies. 2,4,11,20,23,26,27 In conclusion, the results of this study suggest that patient-reported duration of symptoms, preoperative walking distance and disease severity are predictors of outcome in patients treated surgically for degenerative cervical myelopathy. Our findings also suggest that patients with less severe myelopathy and with shorter duration of symptoms are more likely to be satisfied with the surgical treatment, although patients irrespective of degree of disease severity may benefit from surgery.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, the results are consistent with previous, smaller, studies. 2,4,11,20,23,26,27 In conclusion, the results of this study suggest that patient-reported duration of symptoms, preoperative walking distance and disease severity are predictors of outcome in patients treated surgically for degenerative cervical myelopathy. Our findings also suggest that patients with less severe myelopathy and with shorter duration of symptoms are more likely to be satisfied with the surgical treatment, although patients irrespective of degree of disease severity may benefit from surgery.…”
Section: Discussionmentioning
confidence: 57%
“…Type of surgery was not a predictor of outcome in accordance with recent studies. 26,27 This study has some limitations. First, it is retrospective in nature and therefore prone to selection bias.…”
Section: Discussionmentioning
confidence: 95%
“…Both groups experienced statistically significant improvement in all outcome measures. The clinical improvement is, however, modest, and the study population as a whole did not meet the recently suggested MCIC for NDI, NRS pain scores, and EQ-5D in a study from the Swedish Spine Registry [29]. One could argue that MCIC is of lesser importance given the often progressive nature of DCM [7].…”
Section: Discussionmentioning
confidence: 84%
“…There have been no long-term follow-up studies on the clinical and radiologic results of UBEL in the treatment of CS, particularly the development of sagittal imbalance. In a two-year follow-up study, conventional laminectomy with instrumented fusion and laminectomy alone in degenerative cervical myelopathy (DCM) revealed similar effectiveness [ 18 ]. Dios compared patient-reported 5-year clinical results between conventional laminectomy alone and laminectomy with instrumented fusion in patients with DCM and found no important differences [ 19 ].…”
Section: Discussionmentioning
confidence: 99%